Can routinely collected primary healthcare data be used to assess Aboriginal children's health and wellbeing longitudinally? A retrospective analysis of electronic medical records from an Aboriginal community-controlled health service in Central Australia - Catherine Lloyd-Johnsen; John Boffa; Vahab Baghbanian; Rachel Walpole; Shuaijun Guo; Sandra Eades; Anita D'Aprano; Sharon Goldfeld (International Journal of Population Data Science, 2025)
Introduction Electronic medical records (EMR) are an essential tool in modern healthcare, providing a centralised source of patient information. Longitudinal analysis of EMRs can identify opportunities for targeted interventions to improve health outcomes for children. However, the research value of EMRs is contingent on data quality and completeness.